Il diario di Giovanni Maria Parenti sul viaggio verso il Regno d’Ungheria (1486) - Kuffart, Hajnalka (Verbum – Analecta Neolatina, 2022)
Giovanni Maria Parenti was a learned cleric, poet and grammarian from Modena who wrote a biography of the city’s patron saint, St Geminianus, printed in 1495. It is less well known that he also participated in a mission, sent to Hungary by Duke Ercole I d’Este in 1486 headed by the orator Cesare Valentini. Parenti compiled a diary on their journey from Venice to the Hungarian royal court. The twelve-page manuscript is preserved in the State Archives in Modena. The text is not a simple list of places seen, but a lively and eventful account in which anecdotes, praise and sometimes even sharp criticism of the circumstances observed appear. This paper deals with the content of the document, the historical context, and makes an edition of the original text. The final table collects those Valentini letters that are written by Parenti’s hand.